VD_FINDINFO HC / 2012 / 411 vom 21. Mai 2012 - VD Tribunal cantonal (2012)
AVOCAT D'OFFICE, HONORAIRES, INDEMNITÉEN GÉNÉRAL, FRAISEN GÉNÉRAL | 110 CPC (CH), 119 al. 3 CPC (CH), 122 CPC (CH), 319 let. b ch. 1 CPC (CH), 321 al. 2 CPC (CH), 39 al. 5 CDPJ, 2 al. 1 RAJ, 3 al. 3 RAJ